How to Discuss Failure—and Not Get Fired! Lessons from a 2011 Human Development Forum Session - Voytsehovska, Galina (World Bank, Washington, DC, 2012)
Any organization can be good at discussing its successes and good practices. But can it be a truly effective agent for learning and change if success is all it discusses? Doesn't continual learning require being open about mistakes having the courage to talk about them so they can be corrected and not repeated? An organization can be more effective if its staff takes individual responsibility for creating a culture in which risk taking is not only tolerated but also encouraged, and failure is openly discussed. Some experts ascribe about 80 percent of the barriers to an organization's success to issues associated with organizational culture the way it does business, including how it learns from its mistakes and failures. Organizations that openly discuss mistakes and shortcomings tend to get better, become more innovative, and have greater impact. The 2011 Human Development Forum featured a FAILFaire type session, 'how learning from failure can make project success more likely.' This smart lesson grew out of staff requests for follow-up information from that session.